Li+ Extraction/Insertion Reaction with Li1.5Ti1.625O4 Spinel in the Aqueous Phase - Jiang, Jinhe (Asian Journal of Chemistry, 2012)
Spinel-type metal oxides, lithium-titanium oxide (Li1.5Ti1.625O4), was prepared by a solid state reaction crystallization method. The extraction/insertion reaction with this material was investigated by X-ray, saturation capacity of exchange and Kd measurement. The experimental results have proved that the acid-treated sample has a capacity of exchange 6.1 mmol g-1 for Li+ in the solution, the chemical analysis showed that the Li+ extraction/insertion progressed mainly by ion-exchange mechanism and surface adsorption.